2013
DOI: 10.1371/journal.pone.0060690
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Characterization of the MinC-FtsZ Interaction in Bacillus subtilis

Abstract: Cell division in bacteria is regulated by proteins that interact with FtsZ and modulate its ability to polymerize into the Z ring structure. The best studied of these regulators is MinC, an inhibitor of FtsZ polymerization that plays a crucial role in the spatial control of Z ring formation. Recent work established that E. coli MinC interacts with two regions of FtsZ, the bottom face of the H10 helix and the extreme C-terminal peptide (CTP). Here we determined the binding site for MinC on Bacillus subtilis Fts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 65 publications
1
26
0
4
Order By: Relevance
“…In this study, it was proposed that MinC severs FtsZ polymers by specifically breaking the interaction between FtsZ and GDP present in polymers and the adjacent FtsZ molecule through this ␣-helix. A more recent mutational study on Bacillus subtilis FtsZ found mutations that conferred resistance to MinC in a different, more lateral region of FtsZ than in E. coli, suggesting that the MinC inhibition mechanism may be different in this organism (27).…”
Section: Minc Is the Component Of This System That Effectively Interamentioning
confidence: 99%
“…In this study, it was proposed that MinC severs FtsZ polymers by specifically breaking the interaction between FtsZ and GDP present in polymers and the adjacent FtsZ molecule through this ␣-helix. A more recent mutational study on Bacillus subtilis FtsZ found mutations that conferred resistance to MinC in a different, more lateral region of FtsZ than in E. coli, suggesting that the MinC inhibition mechanism may be different in this organism (27).…”
Section: Minc Is the Component Of This System That Effectively Interamentioning
confidence: 99%
“…The Min system in E. coli consists of the three proteins MinC, MinD and MinE [15, 16], and has been studied extensively both experimentally [17-29] and theoretically [29-35]. MinC is the inhibitor of Z-ring formation, inhibiting the bundling of FtsZ filaments [22, 36-39]. MinC is localized through MinD, a protein that belongs to the WACA (Walker A cytomotive ATPase) family [40, 41].…”
Section: Introductionmentioning
confidence: 99%
“…FtsZ Blasios V., et al, 2013); além disso, estudos mais recentes sugerem que MinC também afeta as interações longitudinais que formam o protofilamento (Shen B. e Lutkenhaus J., 2010;Hernández V. et al, 2013, Arumugam S. et al, 2014. MinC é um dímero que consiste em dois domínios ligados por uma alça flexível, ambos os quais têm atividade inibitória de divisão no contexto correto (Hu Z. et al, 1999;Shen B. e Lutkenhaus J., 2009;Shen B. e Lutkenhaus J., 2010).…”
Section: Estudos Mostraram Que Minc Parece Afetar a Associação Lateraunclassified
“…Sabe-se também que o verdadeiro inibidor é a proteína MinC (de Boer P. et al, 1990), e que ela só inibe a divisão na ausência de MinD quando é superexpressa ~50 vezes acima dos níveis endógenos (de Boer P. et al, 1992) (Johnson J. etal., 2002) e a proteína ZipA é requerida para esse recrutamento (Johnson J., et al, 2004 (Blasios V. et al 2013) …”
Section: Importância Da Localização De Minc Na Membranaunclassified
See 1 more Smart Citation